PRINCIPAL'S STRATEGY IN IMPROVING THE QUALITY OF ISLAMIC RELIGIOUS EDUCATION LEARNING AT MUHAMMADIYAH 2 SENIOR HIGH SCHOOL IN SURAKARTA - Oktaviyani, Rissa; Ali, Mohamad (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to: (1) Identify the strategies used by the school principal to improve the quality of Islamic Religious Education learning at SMA Muhammadiyah 2 Surakarta, (2) Identify the factors that support and hinder the strategies used by the principal of SMA Muhammadiyah 2 Surakarta. This type of research employs qualitative research. The design of this study is a case study. The research subjects include the principal, Islamic religious education teachers, and students. Data collection techniques with an interactive model include data collection, reduction, data presentation, and conclusion drawing. The validity of the data is ensured through triangulation of data sources and triangulation of methods. The results of the study indicate that: (1) the principal of SMA Muhammadiyah 2 Surakarta implements various efforts to enhance the quality of Islamic Religious Education learning, such as training for educators, the use of technology, strengthening Islamic values, and routine guidance. These steps play a role in improving teacher competence and students' enthusiasm for learning. (2) The success of this strategy is supported by the active role of teachers, the availability of facilities and infrastructure, and the commitment of school principals. However, there are several challenges, such as lack of student participation, budget limitations, and obstacles in the application of learning technology.